Dynamics of intraerythrocytic parasite infections in the Java common palm civet (Paradoxurus hermaphroditus) - Putri, Maritrana; Cahyaningsih, Umi; Ekastuti, Damiana Rita; Tarigan, Ronald; Achmadi, Pudji; Bustamam, Isdoni; Santoso, Koekoeh; Suprayogi, Agik; Maheshwari, Hera; Satyaningtijas, Aryani (ARSHI Veterinary Letters, 2024)
Over seven weeks, this study investigated intraerythrocytic parasitic infections in the Java common palm civet (Paradoxurus hermaphroditus). Blood samples were collected immediately after the civet had been brought from its natural habitat. Following the 30-day adaptation period, additional samples were collected weekly. Our findings revealed infections with Babesia sp., Theileria sp., and Anaplasma sp., with infection rates being the highest for Anaplasma sp. (0.35 ± 0.05)%, followed by Theileria sp. (0.12 ± 0.05)%, and Babesia sp. (0.03 ± 0.02)%. Throughout the study period, the infection rates of Babesia sp. and Anaplasma sp. decreased, whereas Theileria sp. showed an increasing trend until the conclusion of the study.